The Diagnostic Value of Thrombocytosis in Children with Upper Urinary Tract Infection - خوري, مها; غانم, عبد المنعم; كعيد, يمامة (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: Urinary tract infections are very common in childhood (especially under the age of 5 years) and because of the large number of complications resulting from it (renal failure – hypertension- kidney scarring) had to be diagnosed and early treatment, although that urine culture is the standard Golden diagnosis, but its results are late to appear, Many studies have indicated an accompanying increase in platelet counts in urinary tract infections, so that platelet counts may be a vital indicator directed to it without asylum to the costly analyzes in its diagnosis. Objective: the objective of the following study is to assess the sensitivity and specificity of the plate count (PLT) in UTI. Methods: The study included 65 Patients (14 males, 51females) They were between (3-6) year with upper urine tract infections were diagnosed through symptoms, urological test, Serum tests, and radiology, who were admitted to the pediatric department at Tishreen University Hospital in Lattakia City. PLT was obtained through a complete CBC blood count (sensitivity and sensitization), and comparison of the ratio Percentage of Thrombocytosis between urine culture with Gram-positive germs and Gram-negative germs. Results: The study showed a good sensitivity=80.39% [75–84] to platelet counts compared to urine culture. it also showed statistically significant paper p-value=0.003 between platelet count and type of pathogen (positive or negative Gram) and the increase was more favorable to positive urine culture. Also showed that the average value of platelets is higher in culture a positive gram 521.9±90.9 x103 platelet/mcl than in gram negative 432.3±73.5 x103 platelet/mcl. Conclusion: higher Platelet numbers are a good analysis or sensitivity for the diagnosis of upper urinary tract infection in children with reliable urinary symptoms to start treatment. So that we get the results of culture urine .and the higher platelet count must be taken gram positive bacteria into account.